Implicit-implicit and parametric-implicit surface intersections in Euclidean n-space - Düldül, Mustafa; Özcetin, Bedia Merih (UNIV TARTU PRESS, 2023)
In this paper, we study the intersection problem of two sur-faces in which at least one surface is given by its implicit equation in Euclidean n-space. We first obtain the curvatures of the transversal in-tersection curve of two implicit surfaces. Later, we study the transversal intersection of parametric-implicit surfaces in n-dimensional Euclidean space. Finally, we present examples as applications of the given methods.
Keywords: Curvatures; Frenet vectors; implicit curve; surface-surface in-tersection; transversal intersection; DIFFERENTIAL GEOMETRY; CURVES; HYPERSURFACES; CURVATURE; FORMULAS; R-4; Mathematics